Design and implementation of EMRC web-based portal - Mallo-Eustaquio, Geraldine G.; Pascua, Sonia M.; Dorado, Dan Anthony D. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2018)
The Educational Media Resource Center (EMRC) Web-Based Portal's design and implementation was proposed and described in this paper. Rapid Application Development (RAD) was the methodology used to described the systematic approach of the development. The web portal was developed using programming platforms such as HTML, CSS, Javascript, and PHP the frontend of the system and MySQL was used for its database. The model of the web portal was designed using the Unified Modeling Language (UML) which includes use-case diagram, activity diagram and class diagram. EMRC web-based portal was tested and evaluated with the checklist type questionnaire incorporating the standard of ISO 25010:2011.
From the result of the testing and evaluation of the system, the prominent category of the EMRC web-based portal was the security of the system with the weighted mean of 4.83, followed by the functional suitability with the weighted mean of 4.79, maintainability and portability with the weighted mean of 4.78, usability with the weighted mean of 4.77, reliability ranked sixth with the weighted mean of 4.75, performance efficiency ranked seventh with the weighted mean of 4.74 and the least was the system's compatibility with the weighted mean of 4.67. Results of the evaluation found out that (1) the design of the EMRC web-based portal was effective in creating the web-based portal as it produced a functional, capable and effective web portal; (2) it is important and a great advantage to have an effective and advanced tool to offer library services as it benefits both the EMRC staff and the library patrons; and (3) the result of the evaluation clearly showed areas for improvement of the EMRC web-based portal.
With the results of the evaluation of the EMRC web-based portal the following were the emanated conclusions and recommendations: (1) advanced system like the EMRC web-based portal is a must have in libraries to deliver services for the library patrons in today's generation where everyone accesses the internet or the web for the search of knowledge, (2) audiovisual management system of the EMRC web-based portal helped the EMRC staff in properly handling and organizing its AV collection, (3) the EMRC web-based portal provides online reservation of facility, collection and equipment, and has established the shorter time spent in the reservation process, (4) the provision of search and view to the AV collection and the calendar/schedule of reservations brought a great advantage to library patrons in accessing information remotely, and (5) the communication medium in the EMRC web-based portal has a significant value in meeting the gap of communication between the EMRC staff and its stakeholders.
Special Problem (Master of Library and Information Science)--University of the Philippines Diliman
Keywords: Web-based porta -- Design and implementation; Educational Media Resource Center -- Design and implementation